2016
DOI: 10.1097/mco.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Protein anabolic resistance in cancer

Abstract: Purpose of review Preventing unintentional weight and muscle loss is of crucial importance to maintain the condition and well-being of patients with cancer, improve treatment response and tolerance, and prolong survival. Anabolic resistance might explain why some cancer patients do not respond to nutritional intervention but does recent evidence actually support this? We will discuss recent literature that cast doubt on attenuated anabolic potential in cancer. Recent findings Although anabolic resistance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Therefore, what works in cancer cachexia should be applicable to PICS. Recent studies have shown a linear relationship between dietary amino acid intake and net protein anabolism in patients with advanced cancer (including non–small cell lung cancer and pancreatic cancer) similar to that observed in healthy controls 21 . These data support the recent guideline recommendation that cancer patients should consume at least 1.2–2.0 g/kg/d of protein 22 .…”
Section: Nutrition Supportsupporting
confidence: 75%
“…Therefore, what works in cancer cachexia should be applicable to PICS. Recent studies have shown a linear relationship between dietary amino acid intake and net protein anabolism in patients with advanced cancer (including non–small cell lung cancer and pancreatic cancer) similar to that observed in healthy controls 21 . These data support the recent guideline recommendation that cancer patients should consume at least 1.2–2.0 g/kg/d of protein 22 .…”
Section: Nutrition Supportsupporting
confidence: 75%
“…Previous studies have shown that a lower ΔPMI (likely, patients with sarcopenia or cachexia) results in poor prognosis for patients with solid cancer 13 , 14 . In other words, cancer and inflammation due to cancer cachexia must be considered nutrition risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…A stable isotope investigation estimated that, in pancreatic cancer, patients experiencing an ongoing inflammatory response, 2.6 g of muscle protein would need to be catabolised to synthesise 1 g of the positive acute phase reactant fibrinogen, if food was not consumed . In addition, older patients and patients with advanced cancer might suffer from anabolic resistance. That is, although their anabolic capacity is intact, a larger, sufficient dose of amino acids is required to achieve a typical anabolic response .…”
Section: Protein Anabolismmentioning
confidence: 99%